Organoleptic Analysis of Processed Beef Meatball Products Using the Analytic Hierarchy Process: A Case Study of “Bakso Roso” - Mooduto, Lisna; Dako, Safriyanto; Sahara, Laode (International Journal of Technology and Education Research, 2025)
Processed beef meatballs are widely consumed food products whose quality is largely determined by their sensory attributes. This study aims to analyze the organoleptic quality of beef meatball products at Bakso Roso Restaurant in Gorontalo Regency, focusing on appearance, aroma, taste, and texture. This research addresses a gap in previous studies, which typically rely on conventional sensory tests without applying a structured prioritization method. The study site was purposively selected based on branch availability, accessibility, modern facilities, and certified operations. Primary and secondary data were analyzed using the Analytic Hierarchy Process (AHP) to determine the relative weight of each criterion. The results show that taste is the most influential attribute (0.402), followed by aroma (0.294), texture (0.203), and appearance (0.100), with an inconsistency value of 0.02 indicating reliable judgments. Among product alternatives, Bakso Tenis ranks highest (40.2%), followed by Bakso Urat (29.4%). These findings highlight the dominant role of taste and aroma in shaping consumer preferences and provide a structured basis for product development through AHP-based organoleptic prioritization.